Pengaruh Kredit Macet, Jumlah Nasabah, dan BOPO Terhadap Profitabilitas PT Pegadaian Area Denpasar 1 - Ni Made Dwi Cahyani; I. B. Made Putra Manuaba (Universitas Warmadewa, 2026)
This study aims to provide empirical evidence on the impact of non-performing loans, the number of customers, and the BOPO ratio on profitability. The research focuses on PT Pegadaian Area Denpasar 1 during the 2021-2023 period, comprising 73 outlets. The sampling technique used is purposive sampling, selecting 47 outlets that experienced non-performing loans during the specified period as the research sample. This selection resulted in 141 data samples for analysis. The data used in this study are secondary data obtained from the financial reports of PT Pegadaian Area Denpasar 1 for the 2021-2023 period. Data analysis was conducted using multiple linear regression, along with F-tests, t-tests (hypothesis testing), and the coefficient of determination test. The results indicate that non-performing loans do not affect profitability. Meanwhile, the number of customers has a positive and significant impact on profitability, whereas the BOPO ratio has a negative and significant effect on profitability.